Peningkatan Kinerja Guru Sekolah Dasar Melalui Manajemen Kepala Sekolah di SDN Pengantingan Batang Arah Tapan - Suhermawati, Denada Violin; Nuzuli, Ahmad Khairul; Oktaviana, Winda (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2023)
The motivation behind this examination is to figure out the preparation, execution, assessment and arrangements in working on the exhibition of grade teachers. This study utilizes a subjective methodology. The assortment of information got from different sources, foundations, and different techniques in this examination is through library research. The consequences of this review demonstrate that working on the presentation of primary teachers through the administration of the head at SDN Pengantingan Batang Arah Tapan, to be specific in arranging the school chief makes a yearly everyday schedule (RKTS) that concerns 8 instructive norms, gives SKP rules (representative execution focuses) toward the starting year as a rule for educator evaluation by school directors and DP3 which concerns instructor conduct appraisal, by and by holding and including instructors in logical gatherings like instruction and preparing (redesigning/inservice preparing, studios and courses), in the assessment the Chief regulates the training of the educators (class visit strategies, confidential discussions, and gathering conversations), as well as endeavors made by the Head as a supervisor in further developing execution is to fabricate great correspondence with all educators in building a useful work culture.